Finding of an early mural painting in Huaca Tomabal, Viru Valley, Peru - Castillo Luján, Feren (2022)
In this brief fieldwork report is presented a preliminary study of the huaca Tomabal (VV 118-4: 9) in the Virú valley that unfortunately was partially destroyed with heavy machinery by farmers. Fortunately, an ornate surface with its respective stratigraphy was preserved. Indeed, it is noted the existence of five superimposed buildings with construction techniques typical of the Final Archaic and Formative periods that appear on the south face of the affected mound. The most surprising issue is the discovery of a painting wall with the image of an anthropomorphic being that apparently holds a ceremonial knife in one of its extremities. This early wall decoration is unique in the Virú Valley, so it deserves attention in future research work.